Relationship between genotype, phenylalanine hydroxylase expression and in vitro activity and metabolic phenotype in phenylketonuria - Himmelreich, Nastassja; Shen, Nan; Okun, Jürgen G.; Thiel, Christian; Hoffmann, Georg F.; Blau, Nenad (Molecular genetics and metabolism, 2018)
Residual phenylalanine hydroxylase (PAH) activity is the main determinant of the metabolic phenotype in phenylketonuria (PKU). The genotypic heterogeneity of PKU, involving >1000 PAH variants and over 2500 different genotypes, makes genotype-based phenotype prediction challenging. While a relationship between PAH variants and the metabolic phenotype is well established, we questioned the importance of PAH expression and residual in vitro activity for the metabolic phenotype. Thirty-four PAH variants (p.F39L, p.A47V, p.D59Y, p.I65S, p.R68G, p.R68S, p.E76G, p.A104D, p.D143G, p.R155H, p.R176L, p.V190A, p.G218V, p.R241C, p.R243Q, p.P244L, p.R252W, p.R261Q, p.E280K, p.R297H, p.A300S, p.I306V, p.A309V, p.L311P, p.A313T, p.L348V, p.V388M, A403V, p.R408Q, p.R408W, p.R413P, p.D415N, p.Y417H, and p.A434D) were transiently transfected into COS-7 cells, and expression of PAH was investigated. Expression patterns were compared with in vitro PAH activity and allelic phenotype values (APVs). In vitro PAH activity was significantly higher (p<.01) in variants associated with mild hyperphenylalaninemia (PAH activity=52.1±8.5%; APV=6.7-10.0) than that in classic PKU variants (PAH activity=21.1±7.0%; APV=0-2.7). Mild PKU variants (PAH activity=40.2±7.6%; APV=2.8-6.6) were not significantly different from mild hyperphenylalaninemia, but there was a difference (p<.048) compared with classic PKU phenotypes.
Available online 23 June 2018
Gesehen am 15.01.2020